Three new species of the water strider genus Rhyacobates Esaki, 1923 (Hemiptera: Gerridae) from Vietnam - Tran, A.d.; Nguyen, X.q. (Zootaxa, 2016)
Three new species: Rhyacobates zetteli sp.n., R. angustus sp.n., and R. constrictus sp.n., all from mountainous areas of northern Vietnam, are described. With these new taxa, a total of six species of Rhyacobates has been recorded from Vietnam. A key to species of Rhyacobates occurring in Vietnam is provided.